Role of the Indian Association of Preventive and Social Medicine (IAPSM) in Combating Antimicrobial Resistance (AMR) - Purushottam Giri; Venkatesh Karthikeyan (Healthline)
Antimicrobials are medicines used to prevent and treat infectious diseases in humans, animals, and plants. They include antibiotics, antivirals, antifungals, and antiparasitics. However, the effectiveness of these medicines is under threat due to the growing issue of Antimicrobial Resistance (AMR). Antimicrobial Resistance occurs when bacteria, viruses, fungi, and parasites evolve and no longer respond to antimicrobial treatments, rendering these drugs ineffective. This makes infections increasingly difficult, or even impossible, to treat, thereby raising the risk of disease spread, severe illness, disability, and death. Although AMR is a natural process driven by genetic changes in pathogens, its acceleration is largely fueled by human activity, particularly the misuse and overuse of antimicrobials across various sectors. As AMR continues to pose a global health threat, coordinated efforts to combat it have become crucial. Hence we are exploring the pivotal role of community medicine / preventive and social medicine (PSM) in addressing the global challenge of antimicrobial resistance.